The space of popular education in contemporary times - Jean Louis GUEREÑA (Historia de la Educación, 2013)
Undoubtely, the History of Popular Education represented historically a collection of very various initiatives, but globally characterized by its nature situated out of the formal educational system and by the social origin of its public, coming from the lower classes. This special issue offers some comparatives studies (or which enable at least to compare several similars experiences in different situations, as for Popular Universities), analyses of some forms of Catholic Popular Education and of spaces of popular sociability, as formal (institutional) as informal (spontaneous), set of works that shows the actual researchs in the field of Popular Education.